Strength Characteristics of Clay Soil Reinforced with Natural Fibers - Abood, Mazin J.; Shakir, Ressol R. (Basrah Journal for Engineering Sciences, 2023)
The trend of using natural fibers in geotechnical engineering has become of great interest to improve weak soils due to some of its advantages such as local availability, environmental friendliness, and lower cost. In this study, a set of unconfined compression strength and direct shear tests were conducted to evaluate the performance of Al-Nasiriya clayey soil reinforced with natural fibers. Three different types of natural fibers were investigated as sustainable ones, including wheat straw fiber and palm frond fiber, as well as imperata cylindrica fiber. The effects of various fiber contents (0.25 %, 0.5 %, 0.75 %, and 1 %) and lengths (20 mm, 30 mm, and 40 mm) were experimentally evaluated. The results indicated that the compressive strength increased significantly with the increase of fiber content and length up to an optimum value and then decreased. The optimum fiber content and length were 0.5 % and 30 mm, respectively. Compared to the unreinforced soil, the compressive strength values at the optimum content and length increased by 102 %, 126 %, and 66 % for samples reinforced with wheat straw, palm fronds, and imperata cylindrica fibers, respectively. The shear properties improved due to soil reinforcement with natural fibers. Compared to the unreinforced soil, the internal friction angle of the samples reinforced with wheat straw, palm fronds, and imperata cylindrica fibers increased by 17.7 %, 42 %, and 9 %, respectively. Forever, the cohesion and shear strength are also improved due to inclusion of natural fibers.